The Concept of Grateful in Qs: Al-Ibrahim [14]:7 (Application of Ma'na-Cum-Maghza Theory) - Rosyda 'Aqila (At-Tahfidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
This research will answer the phenomenon of insecurity that can affect the fear and anxiety that occurs in individuals who are not satisfied by comparing them with the achievements in their environment. This insecure attitude is, of course, a problem that must be immediately eradicated so that it does not spread to millennials and the gen-Z Generation. Through QS. Ibrahim[14]:7 with the application of the theory of Ma'na-cum-maghza, solutions to the problem of insecurity will be seen. This study uses library research through hadith literature, interpretation, and syi'ir jahiliyyah to produce a transformation of the concept and meaning of gratitude in three aspects, namely the actualization of positive values in gratitude, involving God, and prudence that have an impact on aspects of gratitude. mental, health, and self-confidence